Characterization of Pulmonary Function in Colombian Covid-19 Survivors; [Caracterización de la Función Pulmonar en Los Sobrevivientes Colombianos de la Covid-19] - Aedo-Munoz, E (Universidad de Antioquia, 2024)
Introduction: SARS-CoV-2 acutely affects human pulmonary function, and respiratory alterations may persist after overcoming the infection. Objectives: To characterize the pulmonary function among Colombian survivors of COVID-19. Methods: A pilot study was conducted where pulmonary function was assessed using a MiniBox™ device, aerobic fitness with a six-minute walk test, and fatigue perception with the Multidimensional Fatigue Inventory (MFI-20). Results: Out of an initial group of 70 participants, only 39 completed the study, with a disease course ranging from mild to moderate. Women comprised the majority (51%) of the participants, and no abnormal values were found in pulmonary function. The total fatigue score was 39 ± 9.2; for general fatigue, it was 5 ± 0, the same as for physical fatigue (5 ± 0); for mental fatigue, the score was 8.56 ± 3.5; for reduced activity, it was 11.2 ± 2.96, and for reduced motivation, it was 9.38 ± 4.4. Additionally, the peak oxygen co sumption (VO2 peak) was 19.51 ml/kg/min ± 2.8 ml/kg/min. Conclusions: Pulmonary function and fatigue levels in Colombian COVID-19 survivors residing in Bogotá who did not require ventilatory support were normal according to the tests performed, while cardiopulmonary fitness was low. © 2024 Universidad de Antioquia.